Traditional Knowledge of Wild Edible Plants Used by the People of Lawat, District Neelum, Azad Jammu & Kshmir, Pakistan - Ijaz, Shabir; Perveen, Anjum; Ashraf, Saima; Abid, Roohi; Kousar, Shazia; Abbas, Zaheer; Arslan, Muhammad (Ethnobotany Research and Applications, 2022)
Background: Wild Food Plants (WFPs) are a natural source of food in many rural communities and potential source of local food security. However, over-harvesting and excessive utilization endanger their survival. This study was conducted to document the diversity of wild edible plants along with their customary food uses from Lawat area Neelum Valley, Azad Jammu & Kashmir. Methods: Data on food uses was collected during 5 years observation (2015-2020) by conducting various surveys using semi-structured and freelisting interviews with 70 local participants and self-observations as well. Novelty was checked by comparing the gathered data with the published literature using Jaccard Index (JI). Use-value (UV) was used to check the relative importance of useful plants. Results: A total of 61 wild food plants belonging to thirty families were collected and identified. The edible parts of all reported species were consumed as fruits, cooked as vegetable and used in herbal tea or eaten raw. Thirty-two species were used as vegetables, followed by 13 species as fruits, 10 species in herbal tea, and 6 as condiments. Herbs were recorded with a major contribution of 72%; trees and shrubs contributed 11% each while 4.91% fern. A number of young parts (aerial part and leaves) of most species are used as vegetable. All reported parts of plants were frequently utilized by residents as food and maximum plants are available in the months of June-August. Most of the recorded WFPs belonged to Rosaceae (9 species), followed by Polygonaceae (8 species), Lamiaceae (5 species), Brassicaceae, and Amaryllidaceae (4 species each). Conclusion: WFPs still play an imperative role in the local food culture and are primary source of food for food insecure families in study area and traditional knowledge attached to them is astonishing in the region. In this study, many wild food plants along with their customary food uses were recorded for the first time in Lawat area with almost 72% of the species followed by 31% at district level and 23% species from Azad Kashmir. Keywords: Wild food plants, Ethnobotany, Indigenous knowledge, Neelum Valley, Azad Kashmir